Unions and Wage Inequality: The Roles of Gender, Skill and Public Sector Employment - David Card; Thomas Lemieux; W. Craig Riddell (Institute of Labor Economics (IZA), 2018)
We examine the changing relationship between unionization and wage inequality in Canada and the United States. Our study is motivated by profound recent changes in the composition of the unionized workforce. Historically, union jobs were concentrated among low-skilled men in private sector industries. With the steady decline in private sector unionization and rising influence in the public sector, unionization is now five times higher in the public than the private sector in both countries. Though the public sector represents only 15-20% of employment, half of unionized workers are in the public sector. Accompanying these changes was a remarkable rise in the share of women among unionized workers. Currently, approximately half of unionized employees in North America are women. While early studies of unions and inequality focused on males, recent studies examine both and reveal striking gender differences. A consistent - and puzzling - finding is that unions reduce wage inequality among men but not among women. In both countries we find striking differences between the private and public sectors in the effects of unionization on wage inequality. These differences have become more pronounced over time. At present, unions reduce economy-wide wage inequality by less than 10% in both countries. However, union impacts on wage inequality are much larger in the public sector. Once we disaggregate by sector the effects of unions on male and female wage inequality no longer differ. The key differences in union impacts are between the public and private sectors - not between males and females.
Keywords: J31; J45; J51; 330; wage inequality; wage structure; unions; collective bargaining; Canada; United States; public sector